Physicochemical and pharmaceutical properties of cross-linked carboxymethyl rice starch prepared by a simultaneous dual reaction - Ornanong S. Kittipongpatana (2018)
Cross-linked carboxymethyl rice starches (CL-CMRS) were prepared from reactions between a native Klong Luang 1 (KL1) rice starch and varied concentrations (2.5-15% w/w) of sodium trimetaphosphate (STMP) in simultaneous carboxymethylation and cross-linking reactions set up using methanol as a solvent. Physicochemical as well as pharmaceutical properties of CL-CMRS were evaluated in relation to the amount of STMP used and the degree of cross-linking (DCx). At a low DCx, the viscosity of CMRS solution was enhanced through the formation of cross-linked polymeric network and chain entanglement. At higher concentrations in the preparation reaction, STMP caused proportional decreases in the water solubility and [2264]70-fold of the solution viscosity, but promoted swelling and water uptake of the modified starches. Rheological behavior of the nonsoluble but swellable CL-CMRS was similar to that of commercial superdisintegrants sodium starch glycolate (SSG), and cross-carmellose sodium (CCS). The swelling and water uptake of CLCMRS were 5-7 and 6-25 times higher, respectively, than that of the native starch. Disintegration test of tablets containing 1 and 3% w/w of native and modified rice starches showed that M-KL1-5 and M-KL1-10 could be developed as tablet disintegrants. © 2010 AACC International, Inc.